THE EFFECT OF ANIMATED VIDEO–BASED EDUCATION ON HUSBANDS’ ATTITUDES TOWARD THEIR ROLE DURING PREGNANCY: A QUASI-EXPERIMENTAL STUDY - Bunga Poppy Frenisyta Sari; Fransisca Retno Asih; Erlin Novitasari (Jurnal Kebidanan Khatulistiwa, 2026)
Background: Husbands' involvement during pregnancy tends to be low. Lack of husbands' involvement leads to low ANC contacts, which are at risk of pregnancy complications, as well as anxiety and unpreparedness for childbirth. Animated videos are an educational medium that can be used to improve husbands' roles. Purpose: to analyze the effect of animated video-based education on husbands' attitudes toward their roles during pregnancy. Methods: A quasi-experimental study with a non-equivalent control group design was conducted at Rumah Sehat Bunda Fitri, Banyuwangi, Indonesia, in April–May 2025. A total of 62 husbands were selected by purposive sampling and divided into two groups: 31 in the intervention group and 31 in the control group. The intervention group received a seven-day animated video-based education program, 11 minutes and 32 seconds in duration, covering ten domains of husbands’ roles during pregnancy. Results: Attitudes were measured using a questionnaire, and data were analyzed using the Mann-Whitney test, paired t-test, and Wilcoxon signed-rank test. Husbands’ attitudes in the intervention group improved significantly after the intervention, from a mean score of 46.52 to 78.65 (p